Implementation of the 1958 New York Convetion in Several Asian Countries: The Refusal of Foreign Arbitral Awards Enforcement on the Grounds of Public Policy - Rajagukguk, Erman (UI Scholars Hub, 2008)
The Convention on the Recognition and Enforcement of Foreign Arbitral Awards Year 1958 or better known as the New York Convention 1958 until now has ratified by 125 countries including Asian Countries, like Indonesia, China, India, Japan, Korea, and Singapore. Through this convention, the arbitral awards can be implemented in the countries where the assets executed by the mechanism from each country. So, the domestic court of the party of the convention given the rights to refuse the recognition and enforcement of the foreign arbitral awards with the reason of public order. That reasons then be the problems where the civil law system countries will interpret the public order in a different way with the common law system country.